A Study on Third Order Runge-Kutta Techniques for Solving Practical Problems - SENTHILKUMAR, Sukumar (Walailak Journal of Science and Technology (WJST), 2013)
In this paper, an analysis has been carried out to examine Nystrom third order, Heun third order and Classical Runge-Kutta third order methods to solve image processing and numerical problems which are demonstrated in brief. The methods adapted are fully capable to cope with the linearity and nonlinearity of the physical problems with versatile physical nature. Example problems and its corresponding results are exhibited which reveal the efficiency and reliability of the employed techniques. Furthermore, validity of an obtained solution is verified in comparison with the simulation output for an image processing problem and numerically computed results for an engineering problem and initial value problems. doi:10.14456/WJST.2014.88